2004
DOI: 10.1080/10473289.2004.10470877
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Evaluation of H2S and NH3Biofiltration for Two Media Used for Wastewater Lift Station Emissions

Abstract: In this study, biofiltration using a natural wood chip medium and a commercial biofiltration medium was evaluated for the removal of moderate concentrations of hydrogen sulfide (H 2 S) (up to 100 parts per million by volume [ppmv]) in the presence of significant concentrations of ammonia (NH 3 ). These levels were chosen as representative of wastewater lift station emissions in the Brownsville, TX, area. NH 3 -removing portions of the biofilms may compete with H 2 S-removing portions and inhibit H 2 S removal.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 9 publications
(14 reference statements)
0
25
0
Order By: Relevance
“…5). Some researchers have found that removal efficiencies increased when the heights of packing were increased [7,20]. When the heights were reduced to one half in experiment 3, the removal efficiency declined (Fig.…”
Section: Effect Of Packing Media On Fixed-film Bioscrubber Operationmentioning
confidence: 84%
“…5). Some researchers have found that removal efficiencies increased when the heights of packing were increased [7,20]. When the heights were reduced to one half in experiment 3, the removal efficiency declined (Fig.…”
Section: Effect Of Packing Media On Fixed-film Bioscrubber Operationmentioning
confidence: 84%
“…In fact, the relatively low pressure drop compared favorably with the 48 -120 mm H 2 O m Ϫ1 of other studies under similar operating conditions. 7,11,14,34,35 The low pressure drop results may be attributed to the small size of the sulfur particles. Thus, the system did not require extra maintenance like chemical rinsing, backwashing, nutrient limitation, or directionally switching operation to avoid clogging for a long time, 36 -40 and the two-stage biofilter packed with cell-laden GAC was very economic.…”
Section: Pressure Dropmentioning
confidence: 99%
“…[1][2][3][4] Mixed gases containing concentrated H 2 S (Ͼ200 ppmv) and diluted NH 3 (Ͻ80 ppmv) exist in some specific emission sources like wastewater lift stations, sewage treatment plants, and night soil treatment plants. [5][6][7] These emissions, in addition to their own toxicity, constitute a source of olfactory nuisance.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Buisman et al 9 proposed a degradation mechanism, with sulfate as the final product of aerobic sulfide removal by Thiobacillus sp. They also concluded that elemental sulfur was only one intermediate by-product of the total process.…”
Section: Technical Papermentioning
confidence: 98%